2017
DOI: 10.1101/108738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A computational model of shared fine-scale structure in the human connectome

Abstract: Variation in cortical connectivity profiles is typically modeled as having a coarse spatial scale parcellated into interconnected brain areas. We created a highdimensional common model of the human connectome to search for fine-scale structure that is shared across brains. Projecting individual connectivity data into this new common model connectome accounts for over three times more variance in the human connectome than do previous models. This newly discovered shared structure resides in fine-scale local var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…However, there are a variety of ways to construct connectivity targets (cf. Guntupalli et al, 2018); for example, in the context of naturalistic stimuli, vertices with temporal ISCs exceeding some threshold could serve as potentially finer-grained connectivity targets. The second, related concept is that constructing a shared space based on functional connectivity yields subject-specific topographic transformations suitable for aligning response time series.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a variety of ways to construct connectivity targets (cf. Guntupalli et al, 2018); for example, in the context of naturalistic stimuli, vertices with temporal ISCs exceeding some threshold could serve as potentially finer-grained connectivity targets. The second, related concept is that constructing a shared space based on functional connectivity yields subject-specific topographic transformations suitable for aligning response time series.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the characteristic size of misalignments probably represents a limit in terms of the size of functional features we can project from the group back to the subject-level; while the native resolution of the subject-level data may well be higher, methods that work on the functional data alone like ICA-DR or PROFUMO will always struggle in the absence of additional constraints if the misalignments are large enough to mean some regions do not overlap with their group-level homologues at all. Fortunately, recent work has suggested that there is scope to further reduce the size of the residual misalignments [Guntupalli and Haxby 2017], and use multimodal data to help identify regions at the subject-level [Glasser et al 2016a], both of which will be essential parts of the push towards finer spatial scales.…”
Section: Group-level Representa Ons and Inherent Spa Al Scalesmentioning
confidence: 99%
“…Notably however, the multiple recent observations that single functional regions can be manifested as multiple disjoint regions in some subjects, is something that not even advanced functional registration algorithms reliant on diffeomorphic warps can correct for. The minimum requirement for this approach is therefore the use of advanced registration techniques that can non-homotopically reorganise the spatial layout of functional regions, as, for example, introduced by Conroy et al [2013], Guntupalli et al [2016] and Guntupalli and Haxby [2017], or Langs et al [2010].…”
mentioning
confidence: 99%
“…In addition, cross-subject alignment of anatomical features could still be an issue at a "high" resolution. Though a sophisticated multimodal surface normalization procedure (MSM-All) was used by the HCP for this dataset (Glasser et al, 2013), cross-subject alignment issues, however minimal, are still likely to be present (Guntupalli, Feilong, & Haxby, 2018). These factors make for a complicated interpretation of wholebrain activation pattern comparisons at a "fine-grained" resolution near to the vertex or voxel-level, which would not be present a coarser ROI parcellation level.…”
Section: Differences Across Levels Of Resolutionmentioning
confidence: 99%